The Andean science of weaving : structures and techniques of warp-faced weaves - Arnold, Denise Y.; Espejo Ayka, Elvira (London : Thames and Hudson, 2015)
The warp-faced weaves of the Andes are the most complex in the world. While existing studies of Andean textiles use a technical language derived from other textile traditions (mainly tapestry from Europe and the Near East), this book takes as its starting point the technical terms in the Aymara and Quechua languages used by Andean weavers themselves. The result is a completely new way of understanding one of the great craft traditions of the world. Authors Denise Y. Arnold and Elvira Espejo have worked with weavers across the region to understand this technical language and have studied more than 700 textile samples in world-class museums and private collections (including the British Museum, the Victoria and Albert Museum, and collections in Bolivia, Peru, and Chile). 'The Andean science of weaving' is a work of groundbreaking scholarship, technically detailed, but also a celebration of one of the most gorgeous and sophisticated weaving traditions in the world. It will be of great interest to practical weavers, museum curators, anthropologists, art historians, archaeologists, and anyone with a love for Latin America and its rich craft traditions.
boek